2012
DOI: 10.1016/j.neuroscience.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sensitization of histamine-independent itch in mouse primary sensory neurons

Abstract: Overexpression of pruritogens and their precursors may contribute to the sensitization of histamine-dependent and –independent itch-signaling pathways in chronic itch. We presently investigated self- and cross-sensitization of scratching behavior elicited by various pruritogens, and their effects on primary sensory neurons. The MrgprC11 agonist BAM8–22 exhibited self- and reciprocal cross-sensitization of scratching evoked by the protease-activated receptor-2 (PAR-2) agonist SLIGRL. The MrgprA3 agonist chloroq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Most of the GSK101-responsive neurons (79%, 135 of 170), CQ-responsive neurons (83%, 128 of 154), and histamine-responsive neurons (81%, 132 of 163), as defined by the first step in the two-step paired protocol, also responded to capsaicin (Fig. 5, D and E), which is consistent with previous studies (12, 29) and indicates that TRPV1 is broadly distributed in itch-sensing neurons. Furthermore, the data indicated that TRPV4 and TRPV1 activities are present in most sensory neurons that respond to both CQ and histamine.…”
Section: Resultssupporting
confidence: 91%
“…Most of the GSK101-responsive neurons (79%, 135 of 170), CQ-responsive neurons (83%, 128 of 154), and histamine-responsive neurons (81%, 132 of 163), as defined by the first step in the two-step paired protocol, also responded to capsaicin (Fig. 5, D and E), which is consistent with previous studies (12, 29) and indicates that TRPV1 is broadly distributed in itch-sensing neurons. Furthermore, the data indicated that TRPV4 and TRPV1 activities are present in most sensory neurons that respond to both CQ and histamine.…”
Section: Resultssupporting
confidence: 91%
“…This included substances known to activate Mrgprs, such as chloroquine and BAM8-22 (see section IV), and also histamine and serotonin, at least in juvenile mice . In older animals, the cells become more selective most likely by changes in receptor expression (Akiyama et al, 2012). The itch specificity of these neurons was further validated by an elegant gain-of-function experiment.…”
Section: A Mas-related G Protein-coupled Receptors In Sensory Neuronsmentioning
confidence: 91%
“…However, others report separate neural pathways mediating histamine and certain types of non-histamine itch 16,17 . Furthermore, while primary sensory neurons of juvenile mice respond to multiple itch mediators, this non-specificity decreases with age 18 . It remains controversial, therefore, if in the adult there are separate afferents that mediate histamine itch and MrgprA3-dependent non-histamine itch.…”
mentioning
confidence: 98%